TINJAUAN KONDISI FISIK ATLET BOLAVOLI PUTRA SMA NEGERI 1 BATANG GASAN PADANG PARIAMAN - Ilham Hakim; Umar . (Jurusan Kepelatihan, Fakultas Ilmu Keolahragaan, Universitas Negeri Padang, 2019)
The purpose of this study was to determine the level of physical condition of male volleyball athletes at SMA Negeri 1 Batang Gasan Padang Pariaman, including: arm muscle explosive power, leg muscle explosive power, aerobic endurance, and agility. This type of research is descriptive research. Sampling was done by total sampling technique from a population of 12 people. Arm muscle explosive power is measured by one hand medicine ball put test, leg muscle explosive power is measured by a vertical jump test, aerobic endurance is measured by a sleep test, and agility is measured by an agility T test. Data analysis techniques used descriptive statistics using frequency tabulation with percentage calculations. Research result; (1) The level of arm muscle explosive power is obtained on average 4,7008 m in the sufficient category. (2) The level of leg muscle explosive power is obtained on average 95.7366 kg m / sec in the less category. (3) The level of aerobic endurance obtained is an average of 37.0166 ml / kg / min in the moderate category. (4) The level of agility obtained an average of 11.4508 seconds in the category enough